2020
DOI: 10.11604/pamj.2020.37.339.21136
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of alcohol use patterns among university students in Uganda

Abstract: Introduction majority of alcohol use pattern studies among university students are from developed countries. Information about the different alcohol use patterns and their correlates among university students in sub-Saharan Africa is limited. The aim of this study was to examine the prevalence and cardinal demographic and psychosocial factors associated with specific alcohol use patterns among Ugandan university students. Methods a cross section study conducted over 5-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…We reported a high prevalence of AUD in the study population. Our findings are in keeping with previous studies that have documented high prevalence of consumption of alcohol in Uganda [ 48 50 ] with figures as high as 40% in one study [ 51 ]. These findings are in keeping with those of a meta-analysis of the prevalence of AUD (40%) in SSA by Olawole et al (2018) [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…We reported a high prevalence of AUD in the study population. Our findings are in keeping with previous studies that have documented high prevalence of consumption of alcohol in Uganda [ 48 50 ] with figures as high as 40% in one study [ 51 ]. These findings are in keeping with those of a meta-analysis of the prevalence of AUD (40%) in SSA by Olawole et al (2018) [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings corroborate previous research on stressful life events and discrimination as motivations for increased alcohol use ( Keyes et al, 2011 ; Choi et al, 2014 ; Kamulegeya et al, 2020 ; Corbin et al, 2013 ) For instance, prior research found that stress was a key motivator for heavy episodic drinking among university students in Uganda ( Kamulegeya et al, 2020 ). Our qualitative findings corroborate this and suggest that alcohol mis/use may serve as a stress coping mechanism for refugee youth.…”
Section: Discussionsupporting
confidence: 91%
“…While we maintain that most studies exploring university student stress and health outcomes fail to include sub-Saharan African students, there are notable exceptions ( Amponsah and Owolabi, 2011 ; Auerbach et al, 2016 ; Bam et al, 2014 ; Edjah et al, 2020 ; Kamulegeya et al, 2020 ; Misigo, 2015 ) where information that included Kenyan, Nigerian, Ugandan, and Ghanaian students has been published. Studies referring to Ghanaian students have been cited throughout this discussion section, but in terms of non-Ghanaian studies, in Kenya, female students reported higher stress, but a different survey instrument was used ( Misigo, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study surveyed Nigerian students ( Auerbach et al, 2016 ); however, results by country were not listed. In Uganda, of the 1,000 students surveyed, 30.5% reported the presence of depression symptoms and 40.8% indicated high levels of academic stress ( Kamulegeya et al, 2020 ). Unfortunately, the tools used to survey the Ugandan students differed from the current study, so direct comparisons are difficult to make.…”
Section: Discussionmentioning
confidence: 99%